Poof! a bot! - Milgrim, David (Milgrim, David. Adventures of Zip., 2018)
Illustrations and simple text relate how Zip, the unlucky alien magician, zaps a bot and tells it what to do, but the bot does not listen. Includes note to parents, introduction to the books vocabulary, and reading comprehension questions.